(untitled) (Altre Modernità, 2021)
This paper examines the common imagery of the inscriptions found on the walls of some Latin American and European cities. We aim to understand the graffiti and other mural artistic manifestations as an insurgence of the words. In order to reflect critically on these manifestations, we examine how the visual language of graffiti relates to visual art and literature. To this end, we follow Aby Warburg’s Atlas Mnemosyne method to address narrative representations as contemporary generational trends. With the help of the theoretical approach of Walter Benjamin’s studies of art and politics, we intend to reflect on the aestheticization of revolt through the appropriation of public spaces. The central point of the paper is to think about walls as places for experimenting with marginal forms of co-creation that question the strategies of visibility of the urban semiological regime. As a conclusion, we interrogate the aesthetics of the revolt using the notions of territory and contemporary culture. The walls have not only become a space for political struggle, but also supports for creative urban practices where art meets the everyday life.